2017
DOI: 10.1002/hep.29373
|View full text |Cite
|
Sign up to set email alerts
|

YAP suppresses gluconeogenic gene expression through PGC1α

Abstract: Cell growth and proliferation are tightly coupled to metabolism, and dissecting the signaling molecules which link these processes is an important step towards understanding development, regeneration and cancer. The transcriptional regulator Yes-associated protein 1 (YAP) is a key regulator of liver size, development and function. We now show that YAP can also suppress gluconeogenic gene expression. Yap deletion in primary hepatocytes potentiates the gluconeogenic gene response to glucagon and dexamethasone, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 34 publications
4
41
1
Order By: Relevance
“…Another recently reported function of YAP in the liver is the regulation of gluconeogenesis and blood glucose homeostasis [29]. Accordingly, we found decreased expression of key gluconeogenic genes in CAPZ LKO mice (Fig.…”
Section: Capzb Controls Hepatocyte Zonation and Liver Metabolismsupporting
confidence: 62%
See 1 more Smart Citation
“…Another recently reported function of YAP in the liver is the regulation of gluconeogenesis and blood glucose homeostasis [29]. Accordingly, we found decreased expression of key gluconeogenic genes in CAPZ LKO mice (Fig.…”
Section: Capzb Controls Hepatocyte Zonation and Liver Metabolismsupporting
confidence: 62%
“…YAP/TAZ function as transcriptional coactivators together with the TEAD family of transcription factors, and their activity is regulated by upstream inputs including the Hippo cascade, centered on the LATS1/2 kinases [16,17]. In vivo, the function of YAP and of YAP-regulatory inputs has been studied with great detail in the liver tissue, where YAP activation leads to hallmark phenotypes [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…They found reduced expression and function of pericentral genes in CAPZ knockouts. In addition, and in line with earlier work on the repressive role of YAP on gluconeogenic genes, 6 CAPZ knockout livers displayed low expression of these genes, and this was functionally related to decreased steady-state blood glucose levels. Very elegantly, Pocaterra and coworkers also demonstrated that the CAPZ knockout liver phenotype was dependent on YAP.…”
supporting
confidence: 79%
“…In the current study, we use a combination of approaches to reveal that Yap directly induces the glucose transporters to redirect glucose utilization toward anabolism. The switch to anabolic glucose metabolism is supported by the recent demonstration that Yap is able to repress gluconeogenesis via suppression of PGC1α (Hu et al , ). In addition to our studies elucidating how Yap regulates glucose transporters, recent reports demonstrate that Yap directly induces the expression of the amino acid transporters SLC38A1 and SLC7A5 to stimulate cell growth (Hansen et al , ; Park et al , ).…”
Section: Discussionmentioning
confidence: 99%